Significance of amyloid A immunoexpression in the prognosis of renal cell carcinoma. Issue 4 (11th January 2016) - Oz Atalay, Fatma; Aytac Vuruskan, Berna; Vuruskan, Hakan
Abstract : The study investigated immunoexpression of amyloid A (AA) in clear cell renal cell carcinoma (CCRCC) and evaluated its clinicopathologic correlation, particularly in disease progression. Expression of AA protein was evaluated in patients with CCRCC by immunohistochemistry. 146 cancerous tissue samples from 86 male and 60 female patients were studied. The relationship between AA protein expression and TNM stage, nuclear grade, renal capsule invasion, perirenal invasion, and survival of the patients were assessed. Thirty four percent of CCRCC cases were AA positive. The positive AA immunoexpression was related to higher Fuhrman nuclear grade, presence of perirenal invasion of the tumor, and poor survival of patients with CCRCC. There was not any statistically significant difference between patients' gender, status of capsule invasion, and stages of the tumor in terms of AA immunoexpression. Tumor stage (Hazard ratio (HR) = 7.76 (95% CI: 2.43–24.8) for stage 3 and HR = 29.9 (95% CI: 6.97–128.32) for stage 4) and AA immunoexpression (HR = 2.16 (95% CI: 1.01–4.64) were found to be associated with survival of the patients with CCRCC in Cox regression analysis. Immunoexpression of AA was increased in high grade CCRCCs. Immunoexpression of AA was associated with poor survival in patients with CCRCC. Thus, AA staining might be used as a useful immunohistological marker for the prediction of poor prognosis in renal cell cancer.